Comparison and interpretation of freshwater bacterial structure and interactions with organic to nutrient imbalances in restored wetlands - Zheng, Fuchao; Zhang, Tiange; Yin, Shenglai; Qin, Ge; Chen, Jun; Zhang, Jinghua; Zhao, Dehua; Leng, Xin; An, Shuqing; Xia, Lu (Frontiers in Microbiology, 2022)
Chemical oxygen demand to nitrogen (COD/N) and nitrogen to phosphorus (N/P) ratios have distinct effects on bacterial community structure and interaction. However, how nutritional imbalances affect the dynamics of freshwater bacterial assemblages in restored wetlands remains poor understood. Here, the composition and dominant taxa of bacterial assemblages in four wetlands (low COD/N and high N/P (LH), low COD/N and low N/P (LL), high COD/N and high N/P (HH) and high COD/N and low N/P (HL)) were investigated. High COD/N siginificantly increased bacterial diversity, and more than 80% of the dominant taxa were obviously affected by variation in COD/N and N/P. The distribution of bacterial assemblages was mostly driven by variations in ammonia nitrogen (NH4+-N) and electrical conductivity (EC), which collectively explained more than 80% of the variation concerning bacterial assemblages. The cooccurrence network indicated that LH promoted bacterial network compactness and bacterial interaction consolidation. The relationships between nutritional imbalances and bacterial assemblages may provide a theoretical basis for the empirical management of wetland ecosystems.